PENGARUH KARAKTERISTIK SISTEM INFORMASI AKUNTANSI MANAJEMEN TERHADAP KINERJA MANAJERIAL DENGAN DESENTRALISASI SEBAGAI VARIABEL MODERATING - ANIK IRAWATI; RICO ARDIANSHAH (Jurnal Akuntansi dan Keuangan, 2018)
This study was aimed to prove empirically the influence of management accounting information system characteristics consisting of broad scope, timeliness, aggregation, and integration on managerial performance with decentralization as a moderating variable. The independent variables used in this study are management accounting information system characteristics (broad scope, timeliness, aggregation, and integration), and the dependent variable used is managerial performance, and the moderating variable used is decentralization. This study uses primary data in questionnaires distributed on units of PT. Japfa Comfeed Indonesia Tbk Poultry Breeding Division Area Sumatra with respondents 35 middle managers and operational managers consisting of Lampung, Jambi, Padang and Medan. The results of this study indicate that the variable characteristics of information timeliness and aggregation effect managerial performance, while the characteristics of information broad scope and integration has no effect on managerial performance. And characteristics of management accounting information system has an effect on managerial performance. However, after being moderated by decentralization the interaction betweencharacteristics of management accounting information systems to managerial performance has no significant effect.  Keywords: Management Accounting Information System Characteristics, Managerial Performance, Decentralization